Optimization of the Vacuum Microwave Drying of Tilapia Fillets Using Response Surface Analysis - Jianwen Ruan; Guang Xue; Yan Liu; Biao Ye; Min Li; Qing Xu (Foods)
This study looked at how vacuum microwave drying (VMD) affects the quality of tilapia fillets (Oreochromis spp.). It focused on the impact of fillet thickness, microwave power, and vacuum pressure on key quality parameters, such as water activity (Aw), texture, rehydration rate, and whiteness. A series of experiments were conducted with varying fillet thickness (3–7 mm), microwave power (132–396 W), and vacuum pressure (0.03–0.07 MPa) using a Box-Behnken design to optimize drying conditions. The findings revealed that fillets with a thickness of 3 mm had the lowest Aw and the highest hardness, while 7 mm thick fillets had the best rehydration rate, elasticity, and whiteness. Additionally, increasing microwave power caused a gradual decrease in Aw and whiteness, while elasticity, hardness, and the rehydration rate initially increased and then decreased. As vacuum pressure increased, Aw decreased, and both whiteness and elasticity improved. The optimal drying conditions for tilapia fillets were identified as 7 mm thickness, 330 W microwave power, and 0.06 MPa vacuum pressure. Under these conditions, the dried fillets achieved a comprehensive quality score of 93.94. The regression model developed for optimization showed strong predictive performance, with a minimal deviation of only 1.45% from the experimental results, indicating its reliability for predicting drying effects.